Al Qur An Dan Astronomi - Abdul Kadir (STIT Muslim Asia Afrika, 2019)
God reminds us of the many places in the Koran regarding His omnipotence in creating and elevating the heavens firmly and adorned with countless planets and stars, without any differences or defects in the structure of the building.The word as-samaa 'in Arabic generally means natural systems that are above the earth, both near and far away. Therefore, the invitation of the Koran to contemplate the structure of the sky contains recommendations to function the mind in contemplating its laws to be known by means of research or study. The continuity of the structure of natural buildings is one of the conditions of balance and legal order that applies in the universe in accordance with the will and provisions of Allah. The Qur’an repeatedly mentions heaven and earth created for the benefit of humans. In the Qur'an there are several stories that are conveyed so that humanity can take its lessons. The stories leave a number of historical sites including: Ashabul Kahfi Cave, Giza Pyramid and Petra Sand Hill. From these stories, there are several things related to science, such as the meaning of astronomical counts for as long as the young ashabul kahfi sleep, the meaning of the position of the building on the petra dune, as well as the placement of the giza pyramid which is associated with a symbol of constellation.